Zero-Field Nernst Effect in a Ferromagnetic Kagome-Lattice Weyl-Semimetal Co3Sn2S2 - Guin, Satya N.; Vir, Praveen; Zhang, Yang; Kumar, Nitesh; Watzman, Sarah J.; Fu, Chenguang; Liu, Enke; Manna, Kaustuv; Schnelle, Walter; Gooth, Johannes; Shekhar, Chandra; Sun, Yan; et al. (Advanced Materials, 2019)
The discovery of magnetic topological semimetals has recently attracted significant attention in the field of topology and thermoelectrics. In a thermoelectric device based on the Nernst geometry, an external magnet is required as an integral part. Reported is a zero-field Nernst effect in a newly discovered hard-ferromagnetic kagome-lattice Weyl-semimetal Co3Sn2S2. A maximum Nernst thermopower of ≈3 µV K−1 at 80 K in zero field is achieved in this magnetic Weyl-semimetal. The results demonstrate the possibility of application of topological hard magnetic semimetals for low-power thermoelectric devices based on the Nernst effect and are thus valuable for the comprehensive understanding of transport properties in this class of materials.
CRIS-Team Scopus Importer:2022-04-14
Keywords: hard magnets; magnetic Weyl-semimetals; Nernst effect; thermoelectrics; zero-field Nernst thermopower